2012
DOI: 10.4269/ajtmh.2012.11-0168
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Segregation between Two Species of Chagas Disease Vectors

Abstract: Abstract. Triatoma infestans and Panstrongylus megistus are relevant Chagas disease vectors. An apparent segregation among these triatomine species inside human households was suggested to rely on mutual repellence between them. However, P. megistus and T. infestans show aggregation responses to chemical signals emitted by the other species. These findings do not rule out the possibility that stimuli other than chemical signals could mediate repellence when these species exploit shelters simultaneously. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…For example, some species of Triatominae are attracted to the chemical signals left from individuals of the same and of different species 39 . At the same time, in a binary choice experiment involving one or two species, individuals are not able to aggregate (or segregate) in a particular shelter and display therefore a spatial dispersion (equal distribution of individuals between the two shelters) 40 . Our model accounts for these situations even though the feedbacks retained relate to conspecific and heterospecific attractions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some species of Triatominae are attracted to the chemical signals left from individuals of the same and of different species 39 . At the same time, in a binary choice experiment involving one or two species, individuals are not able to aggregate (or segregate) in a particular shelter and display therefore a spatial dispersion (equal distribution of individuals between the two shelters) 40 . Our model accounts for these situations even though the feedbacks retained relate to conspecific and heterospecific attractions.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the shelters, a piece of filter paper (4×6 cm) impregnated with a blend of the five compounds was introduced, while the other shelter contained a piece of filter paper treated with solvent as control. This shelter design ( Figure 1B ) is proven to successfully recruit triatomine bugs [6] , [7] , [23] , [24] , which tend to enter the shelters due to their strong thigmotaxis and intense negative phototaxis [25] .…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of competitive processes in triatomines has been studied through the analysis of interactions between different species in laboratory conditions (Mota & Lorenzo, ), semi‐natural environments (Bar et al ., ; Pereira et al ., ; Oscherov et al ., , ) and in the context of natural colonization and recolonization processes in domestic and peridomestic environments (Cecere et al ., ; Pereira et al ., ). Most of these reports analysed changes in the density of a controlled population of a particular species in the presence of a second species and suggested that individuals presenting higher feeding rates would demonstrate adaptive advantages over those that need more time to attain full alimentation when food is limited.…”
Section: Introductionmentioning
confidence: 99%